Effect of HIV exposure and timing of antiretroviral therapy initiation on immune memory responses to diphtheria, tetanus, whole cell pertussis and hepatitis B vaccines - Omphile E. Simani; Alane Izu; Marta C. Nunes; Avy Violari; Mark F. Cotton; Nadia Van Niekerk; Peter V. Adrian; Shabir A. Madhi (Taylor & Francis Group, 2019)
Objectives: We evaluated memory responses and antibody persistence to diphtheria-toxoid, tetanus-toxoid, whole-cell-pertussis (DTwP), and Hepatitis-B vaccines in HIV-unexposed, HIV-exposed-uninfected and HIV-infected children previously randomized to initiate time-limited ART at 6-10 weeks (ART-Immed) or when clinically/immunologically indicated (ART-Def). Methods: All children received DTwP booster at 15-18 months. Antibodies were measured for pertussis-toxoid, filamentous haemagglutinin (FHA), diphtheria-toxoid, tetanus-toxoid, and hepatitis-B prior to booster, 1-2 weeks post-booster and at 24 months of age. Results: Pre-booster antibody GMC were lower in HIV-infected groups than HIV-unexposed children for all epitopes. Post-booster and at 24 months of age, the ART-Def group had lower GMCs and antibody proportion ≥0.1 IU/ml for tetanus-toxoid and diphtheria-toxoid compared to HIV-unexposed children. At 24 months of age, the ART-Immed group had higher GMCs, and more likely to maintain antibody titres ≥1.0 IU/ml to tetanus-toxoid and diphtheria-toxoid compared to HIV-unexposed children. Compared to HIV-unexposed children, at 15 and 24 months of age, persistence of antibody to HBsAg of ≥10 mIU/ml was similar in the ART-Immed group but lower among the ART-Def group. Antibody kinetics indicated more robust memory responses in HIV-exposed-uninfected than HIV-unexposed children to diphtheria-toxoid and wP. Conclusion: HIV-infected children not on ART at primary vaccination had poorer memory responses, whereas HIV-exposed-uninfected children mounted robust memory responses.